Dynamic service composition for telecommunication services and its challenges - Syed Mustapha, Syed Malek Fakar Duani; Chua, Hui Na * (International Association for Sharing Knowledge, 2014)
As communication networks have evolved towards IP (Internet Protocol) networks, telecommunication operators has expanded its reach to internet multimedia web content services while operating circuit-switch networks in parallel. With the adoption of SOA (Service Oriented Architecture) that enables service capability interfaces to be published and integrated with other service capabilities into new composite service, service composition allows telecommunication providers to accelerate more new services provisioning. From the perspective of telecommunication providers to deliver integrated composite service from different providers and different network protocols, this paper is aimed to present the current service composition based on middleware approaches; discuss the requirements of meeting the challenges; and compare the approaches.